CORRELATION STUDY BETWEEN SERVICE QUALITY AND CUSTOMER LOYALTY IN HOTELS OMACASA IN BENGKULU CITY - Ramadani, Rizki; Andi Azhar (Pedagogic Research-Applied Literacy Journal, 2025)
This research aims to analyze the correlation between service quality and customer loyalty at the Oma Casa Hotel, Bengkulu City. Service quality is measured based on five main dimensions, namely reliability, responsiveness, guarantee, empathy, and physical evidence, while customer loyalty is analyzed through the variables of customer satisfaction, frequency of repeat visits, and the tendency to recommend the hotel to others. This research uses a survey method by collecting data through questionnaires distributed to 100 customers staying at the Oma Casa Hotel. The analysis technique used is Pearson correlation to test the strength and direction of the relationship between service quality and customer loyalty. The research results show that there is a significant positive relationship between service quality and customer loyalty at the Oma Casa Hotel, which indicates that improving service quality can have a direct effect on increasing customer loyalty. These findings provide implications for hotel management to focus more on improving service quality to strengthen relationships with customers and increase repeat visit rate